4.C. Round table: Recovering from the COVID-19 Pandemic: Identifying and Acting Upon Lessons Learned. (20th October 2021) - ,; ,
Abstract: : The COVID-19 pandemic has revealed many gaps and vulnerabilities in health systems and pandemic preparedness in European countries. It has also led to innovation and rapid improvements in certain elements of public health practice. One defining characteristic of the COVID-19 pandemic has been the rapid advance of scientific knowledge, accompanied by high degrees of scientific uncertainty. Each phase (or "wave") of the pandemic has presented unique challenges. This workshop involves public health practitioners from multiple European countries. They will reflect upon some over-arching lessons learned through their experiences in the field, while also alluding to important innovations in public health that should be safeguarded for the future. The panellists will also discuss how lessons learned can be systematically identified and acted upon, through approaches such as after-action reviews (AARs), in order to optimise the public health response to the ongoing COVID-19 pandemic as well as to future ones. The panel discussion format of this workshop adds value to EUPHA 2021 participant through hearing, in a relatively informal format, the experiences from senior staff at national public health agencies from a variety of European countries and contexts. This approach keeps a coherence between speakers will also highlighting the unique challenges posed by specific national contexts. This workshop will also consider how processes such as AARs can be formalised to become routine aspects of public health practice. Particular attention will be paid to challenges and solutions that are similar across national boundaries. During the workshop, the moderator will ensure that the panelists responses are short and succinct. The final 15 minutes will be dedicated to questions from the audience. Speakers/Panelists: Flavia Riccardo ISS, Rome, Italy Ute Rexroth RKI, Berlin, Germany Tanya Melillo Directorate of Health Promotion and Disease Prevention, MSIDA, Malta Mario Fafangel National Institute of Public Health, Ljubljana, Slovenia Key messages: In order to guide the public health response to the COVID-19 pandemic as well as to future pandemics, it is essential to systematically identify lessons learned as well as innovative good practices. Identifying lessons learned, however, is only a first step as it is essential to develop action plans that are supported and endorsed across a wide range of stakeholders.